PELATIHAN HIDROPONIK DI SMAN 1 DENPASAR, BALI - Pharmawati, M.; Wirasiti, N. N.; Wahyuni, I.G.A.S.; Kawuri, R. (Buletin Udayana Mengabdi; Vol 16 No 2 (2017), 2017)
Hydroponic is a technique in horticulture especially for vegetable crop. This technique has several advantages such as balance nutrition, does not require wide land, free from weeds and high productivity. Cultivation of vegetable using hydroponic can be done at house backyard or schoolyard. Therefore, hydroponic need to be introduced to school children. The aim of the activity was to tain highschool students of SMA 1 Denpasar to be able to grow vegetables using hydroponic technique. The methods used in this activity were lecture on types of vegetables, types of hydroponic systems, seedbed development and nutrition, practical class and discussion. Hydroponic system used in practical class was simple technique using floating system with wick. The first activity was attended by 18 students and two teachers. Evaluation was done on the enthusiasm of students during activity and the growth of vegetables planted. Wick using flannel fabric resulted in better growth of vegetables as compare to using stove wick. The second activity was traning using active hydroponic system NFT. The activity was attended by 8 students and two teachers.